Imobilisasi Hasil Samping Pengolahan Limbah Cair Laboratorium Kimia Menjadi Batu Bata Untuk Keamanan Penyimpanan - Taufan Ratri Harjanto; Saipul Bahri (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: The wastewater treatment plant will produce sludge which is discharged directly into the environment can give rise to environmental risk and the health of humans and other living things. The research purposes are to produce brick from immobilization from by-products (sludge) that are effective, easy and environmentally friendly. Method: The study was divided into three stages: (1) initial identification, (2) design and (3) interpretation of results and conclusions. Results: The analysis of bricks made based on the ratio of binder and sludge by 1: 1, 2: 1 and 3: 1, the 16 parameters tested guided by Republic of Indonesia Minister of Environment Regulation number 5 of 2014 Concerning Wastewater Quality Standards, Annex XLVII give : there are two parameters that do not the quality standards: (1) Total Dissolved Solids (TDS) is 4200 mg / l (sample A, ratio of binder and sludge 1:1) and (2) the pH parameter is more than 9 (sample A, B, C, and E). Conclusion: Sludge, stored in the form of bricks is safe.